2023
DOI: 10.1371/journal.pone.0279971
|View full text |Cite
|
Sign up to set email alerts
|

Genetic scores for predicting longevity in the Croatian oldest-old population

Abstract: Longevity is a hallmark of successful ageing and a complex trait with a significant genetic component. In this study, 43 single nucleotide polymorphisms (SNPs) were chosen from the literature and genotyped in a Croatian oldest-old sample (85+ years, sample size (N) = 314), in order to determine whether any of these SNPs have a significant effect on reaching the age thresholds for longevity (90+ years, N = 212) and extreme longevity (95+ years, N = 84). The best models were selected for both survival ages using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 105 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…A significant association with the same set of health variables was also obtained for rs533984 in the MRE11A gene ( p ranging from 0.005 to 0.029) and for rs4977756 in the CDKN2B gene, with higher (better) scores obtained for the less frequent genotypes in both genes. It should be emphasised that in previous research, GG was assigned as a longevity genotype in rs16847897 [ 31 , 32 ] and in rs4977756 [ 33 ], which makes this result of the subjective health and functional ability assessment consistent with the expected longevity of these individuals. However, for rs533984 in the MRE11A gene, better scores were associated with the AA genotype, which was not previously related to longevity [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant association with the same set of health variables was also obtained for rs533984 in the MRE11A gene ( p ranging from 0.005 to 0.029) and for rs4977756 in the CDKN2B gene, with higher (better) scores obtained for the less frequent genotypes in both genes. It should be emphasised that in previous research, GG was assigned as a longevity genotype in rs16847897 [ 31 , 32 ] and in rs4977756 [ 33 ], which makes this result of the subjective health and functional ability assessment consistent with the expected longevity of these individuals. However, for rs533984 in the MRE11A gene, better scores were associated with the AA genotype, which was not previously related to longevity [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the Southern Italian population, the C allele of rs16847897 enhanced the chance of earlier development of Alzheimer’s disease [ 45 ] but did not significantly correlate with human lifespan in a follow-up study [ 46 ]. In a previous study on the same Croatian sample of the oldest-old, we found that the other allele, G, contributed to longevity by increasing the probability of reaching the longevity threshold age of 90 years [ 32 ]. The G longevity allele is a major allele in each of the European populations mentioned above and a minor allele in the Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up study by the same group found that the PLS they derived previously was associated with a favorable metabolic profile [ 31 ]. Another recent independent study in Croatia found evidence that long-lived individuals (90–95 years or older) harbored a unique genetic profile [ 70 ], and yet another recent study involving a German cohort also found evidence for an association between a PLS they derived and longevity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we tested the effect of 43 SNPs, previously reported to have an effect on longevity and associated with genes belonging to different ageing-related pathways, on survival of the oldest-olds, both individually and in SNP-SNP interactions. To this end, we made use of our previously generated dataset on a Croatian sample of individuals aged 85 years and older, which has been used to determine the genetic makeup that contributes to reaching longevity and extreme longevity in the studied sample ( Šetinc et al, 2023 ). Furthermore, the significance of these interactions was tested together with a large set of health status indicators available for the studied population to determine whether the genetic effect was independent of health-related phenotypes.…”
Section: Introductionmentioning
confidence: 99%